Mental health law in New Zealand. (2nd January 2018) - Soosay, Ian; Kydd, Rob
Abstract : New Zealand has an established history of mental health legislation that sits within a framework of human rights, disability and constitutional protections. We outline a brief history of mental health legislation in New Zealand since its inception as a modern state in 1840. The current legislation, the Mental Health (Compulsory Assessment and Treatment) Act 1992, defines mental disorder and the threshold for compulsory treatment. We describe its use in clinical practice and the wider legal and constitutional context which psychiatrists need to be aware of in their relationships with patients.